2019
DOI: 10.1126/sciadv.aax1110
|View full text |Cite
|
Sign up to set email alerts
|

Breathing dissipative solitons in mode-locked fiber lasers

Abstract: Dissipative solitons are self-localized coherent structures arising from the balance between energy supply and dissipation. Besides stationary dissipative solitons, there are dynamical ones exhibiting oscillatory behavior, known as breathing dissipative solitons. Substantial interest in breathing dissipative solitons is driven by both their fundamental importance in nonlinear science and their practical applications, such as in spectroscopy. Yet, the observation of breathers has been mainly restricted to micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
148
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(152 citation statements)
references
References 43 publications
4
148
0
Order By: Relevance
“…Time-stretching methods have been widely employed in the experimental investigation of optical pulses in the fiber lasers by researchers, including the dissipative solitons, 52,129,130 soliton molecules, 131-133 chaotic pulses, 134,135 intermittent pulses, 78,136 transition dynamics, and other nonlinear dynamics. [137][138][139] In 2014, the Raman RW generation in the pulse fiber lasers was provided by the research group of Runge et al 82 By employing the pulse stretching method, the statistical histograms of wave events in more detail were investigated and the spectral evolution of RWs in real time was analyzed. Also in 2014, Lecaplain et al 123 demonstrated RW emission in a fiber laser operating in the NLP regime.…”
Section: Time Stretchingmentioning
confidence: 99%
“…Time-stretching methods have been widely employed in the experimental investigation of optical pulses in the fiber lasers by researchers, including the dissipative solitons, 52,129,130 soliton molecules, 131-133 chaotic pulses, 134,135 intermittent pulses, 78,136 transition dynamics, and other nonlinear dynamics. [137][138][139] In 2014, the Raman RW generation in the pulse fiber lasers was provided by the research group of Runge et al 82 By employing the pulse stretching method, the statistical histograms of wave events in more detail were investigated and the spectral evolution of RWs in real time was analyzed. Also in 2014, Lecaplain et al 123 demonstrated RW emission in a fiber laser operating in the NLP regime.…”
Section: Time Stretchingmentioning
confidence: 99%
“…For our passively mode-locked laser model, we applied the master-equation approach [13], which is one of the main techniques used in the theory of passively mode-locked lasers. Namely, we used the complex cubic-quintic Ginzburg-Landau equation (CQGLE) [1,7]. This continuous model has an analogue in the corresponding lumped model, and the net linear gain/loss parameter (denoted here by θ) is directly related to the small-signal gain of the active fibre, thus it plays alike role to the pump power in the experiment.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…In this paper, we report on the direct experimental observation of breathing DSs in a passively mode-locked fibre laser [7]. Remarkably, in the normal-dispersion regime of the laser cavity, breathers are excited in the laser under the pump threshold for stationary DS mode locking.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the soliton explosion, the breathing soliton becomes broaden and then recovers to its original state instead of exploding in temporal domain. Recently, the temporal and spectral evolutions of breathing soliton have been observed in an Er-doped mode-locked fiber laser by Peng et al [30].…”
Section: Introductionmentioning
confidence: 99%